2022
DOI: 10.1002/cbic.202200342
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the Isocoumarin Derivatives Fusamarins is Mediated by the PKS8 Gene Cluster in Fusarium

Abstract: Fusarium mangiferae causes the mango malformation disease (MMD) on young mango trees and seedlings resulting in economically significant crop losses. In addition, F. mangiferae produces a vast array of secondary metabolites (SMs), including mycotoxins that may contaminate the harvest. Their production is tightly regulated at the transcriptional level. Here, we show that lack of the H3 K9-specific histone methyltransferase, FmKmt1, influences the expression of the F. mangiferae polyketide synthase (PKS) 8 (FmPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…For most of these, expression was generally very low suggesting that additional factors are required to induce their transcription. This is most prominent in the case of the two PKS-encoding genes, PKS17 (FPRN2_14992) and PKS18 (FPRN2_15000), and the remnant of PKS8 (FPRN_15017) [32], all located in close proximity to one another on chromosome 11. None of those genes is derepressed upon relief of H3K27me3 in Δfpkmt6 (Fig 5, highlighted with an asterisk).…”
Section: Loss Of H3k27me3 Results In Increased Bgc Expression In F Pr...mentioning
confidence: 97%
See 1 more Smart Citation
“…For most of these, expression was generally very low suggesting that additional factors are required to induce their transcription. This is most prominent in the case of the two PKS-encoding genes, PKS17 (FPRN2_14992) and PKS18 (FPRN2_15000), and the remnant of PKS8 (FPRN_15017) [32], all located in close proximity to one another on chromosome 11. None of those genes is derepressed upon relief of H3K27me3 in Δfpkmt6 (Fig 5, highlighted with an asterisk).…”
Section: Loss Of H3k27me3 Results In Increased Bgc Expression In F Pr...mentioning
confidence: 97%
“…Next to H3K27me3, another heterochromatic mark i.e., histone H3 lysine 9 trimethylation (H3K9me3), appears to be required for wild type-like SM gene expression in several fungi including Fusarium spp. [22,28,32]. H3K9me3 is a hallmark for constitutive heterochromatin and typically associated with centromeric and gene-poor regions.…”
Section: Introductionmentioning
confidence: 99%
“…Several biosynthetic gene and gene clusters responsible for coumarins and isocoumarins have been discovered [ 23 , 32 , 33 , 34 , 35 ]. In fungi, isocoumarin derivatives are primarily derived from the polyketide pathways, which are typically catalyzed by nonreducing polyketide synthase (nrPKS), containing domains such as starter unit ACP transacylase (SAT), β-ketoacyl synthase (KS), acyl transferase (AT), product template (PT), acyl carrier protein (ACP), methyltransferase (MT), and thioesterase (TE) [ 22 , 23 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it was reported 50 years ago, the biosynthetic pathway has not been revealed yet. Indeed, Atanasoff-Kardjalieff et al , 55 managed to investigate the gene cluster involved in fusamarins biosynthesis. They showed that the FmPKS8 biosynthetic gene cluster (FMN BGC) leads the biosynthesis, which is composed of FmPKS8 (FmFMN1), followed by FmFMN2, FmFMN3, and FmFMN4.…”
Section: General Biosynthetic Pathway Of Fungal Isocoumarinmentioning
confidence: 99%